Penggunaan Video Pada Perangkat Handphone Sebagai Media Penuntun Praktikum Anatomi - Firdaus Firdaus (Fakultas Kedokteran Universitas Riau, 2015)
Evaluation of medical education curriculum by the faculties of medicine in the 21st century shows a reduction in timeallocated for learning of anatomy. Reduction of time allocated for anatomy learning session and the limited numberof instructors require the development of teaching media that have high mobility as one of solutions. This study usedan experimental pretest-postest with control group design method to measure the difference in the level of anatomicalknowledge before and after the anatomy practicum between the two groups of students. Some video on mobile Phone(mobile devices) as a media guide to the anatomy practicum was given to one group of students as a study treatment.Results of Mann-Whitney test showed significant differences level of anatomical knowledge between the two groupsof students, the treatment group had a level of anatomical knowledge significantly better than the control group.Video on mobile devices as a media guide to the anatomy practicum creates students’ level of anatomical knowledgeto be better.